Effect of coenzyme Q10 on tibial fracture resistance in nicotine-exposed rats. - Ruan Henrique Delmonica Barra; Bianca Rafaeli Piovezan; Henrique Rinaldi Matheus; Otávio Augusto Pacheco Vitória; Elisa Mara de Abreu Furquim; Luiz Guilherme Fiorin; Ester Oliveira Santos; Juliano Milanezi de Almeida (PLoS ONE)
The study aimed to evaluate the potential protection against fractures of oral Q10 supplementation in the tibias of rats exposed to nicotine. Nicotine is known to negatively impact bone density and increase the risk of fractures, in addition to affecting other systems such as the gastrointestinal system, impairing its absorption capacity, negatively affecting bone health. To investigate this, eighty male rats were divided into four groups (n = 20) receiving either nicotine hemisulfate or saline solution (SS) for 28 days. Two daily subcutaneous applications were administered accordingly. Concurrently, vegetable glycerin and Q10 gavage began on day "0". SS: the animals in this group received two daily subcutaneous applications of sodium chloride solution during the entire trial period. 30 days after starting the SS applications subcutaneously, the animals received vegetable glycerin daily until the end of the experiment. SS-Q10: the animals received the SS protocol and daily supplementation with Q10 until the end of the experiment. NIC: The animals received the protocol for NIC and vegetable glycerin daily until the end of the experiment. NIC-Q10: The animals received the protocol for NIC and daily supplementation and Q10 until the end of the experiment. Euthanasia occurred at 7 and 28 days after the beginning the gavage. The tibiae collected were processed for morphometric, densitometric, mechanical, and microtomographic (micro-Ct) analysis. A complementary analysis of intestinal changes was performed. The groups that received Q10 showed slightly better results regarding the mechanical resistance and micro-Ct parameters and to intestinal histomorphometry, as compared with groups not supplemented with Q10. Thus, in rats, it can be concluded that coenzyme Q10 exhibited a protective property to the skeletal system and the gastrointestinal tract, even in the presence of nicotine.